Aquaculture effluent reused as a sustainable alternative water supply for landscape irrigation using drip irrigationl - Siak How, Bong (2010)
Aquaculture effluent is the wastewater discharged from fish farm in the industry nourished with nutrients. These are potential pollutants if discharged improperly as overwhelming concentration of nutrients will cause blossom of algae and other aquatic plants and cause eutrophication. At some extend, the water quality of the aquaculture effluent are sustainable to be used as an alternative water supply for landscape irrigation as Nitrogen, Phosphorus and Potassium are the major Tute1fl for p1alfl grQwth. The objective is to 4termine the ainability of aquaculture effluent as an alternative water supply for landscape irrigation under unfertilized condition. With Garden A irrigated with aquaculture effluent and Garden B irrigated with tab water which work as control, the potential of aquaculture effluent can be determined. The overall result for Aquaculture Effluent in terms of water quality are: BOD 13.5±3.64 mg/IL; COD 16.72±0.33mgfL;TSS 28.33±10.8mg/L;TC 0/100ml;Turbidity 64.69±14.2mg/L; Salinity 0.lmgfL; Nitrate 0.36±0.1 7mgfL; Nitrite 7.22*2. l6mgfL; Phosphorus 0.27±0.036mg/L; Potassium 2.59±0.215mg/L while the result for Tab water are: BOD 10.955± 3.13 mg/L; COD 16.67±1.1 5mgfL; TSS 6.83±3.65mgfL;TC 4.8±5.87/100m!; Turbidity 3.31±3.22mgIL; Salinity 0.lmg/L ;Nitrate 0.36±0.17mgfL; Nitrite 4.88±1.73mgfL; Phosphorus 0.1610.08mg/L; Potassium 2.5510.3 mg/L. All the water quality parameters falls into Standard A water quality but Turbidity and Total Coliform doesn't fulfill the requirement of U.S.EPA for landscape irrigation. All the types of plants at Garden A show an advantageous growth compare to Garden B however for most of the plants there is at least one growth parameter that experience slow growth rate. Alternanthera dentata shows the most growth percentage when irrigate with Aquaculture Effluent at a mean of 128.51% for all four parameters followed by Chupea Igneus white 120% and Chupea igneus red 99.53%. These three types of Plants shows 111.0%, 103.48% and 80.47% of growth difference with the ones irrigate with Tab water. It shows that these three types of plants are the most effective landscape plant to be irrigate with AquacUlture Effluent taken from Taman Tasik, Panching with drip irrigation method.